Vaccines in pregnancy: a review of their importance in Brazil - Bricks, Lucia Ferro (Revista do Hospital das Clínicas, 2003)
Neonates and young children remain susceptible to many serious infectious diseases preventable through vaccination. In general, current vaccines strategies to prevent infectious diseases are unable to induce protective levels of antibodies in the first 6 months of life. Women vaccinated during pregnancy are capable of producing immunoglobulin antibodies that are transported actively to the fetus, and maternal immunization can benefit both the mother and the child. With few exceptions, maternal immunization is not a routine, because of the concerns related to the safety of this intervention. Ethical and cultural issues make the studies on maternal immunization difficult; however, in the last decade, the development of new vaccines, which are very immunogenic and safe has reactivated the discussions on maternal immunization. In this paper we present a review of the literature about maternal immunization based on MEDLINE data (1990 to 2002). The most important conclusions are: 1) there is no evidence of risk to the fetus by immunizing pregnant women with toxoids, polysaccharide, polysaccharide conjugated and inactive viral vaccines; 2) most viral attenuated vaccines are probably safe too, but data is still insufficient to demonstrate their safety; therefore these vaccines should be avoided in pregnant women; 3) in Brazil, there is a need for a maternal immunization program against tetanus. Many new candidate vaccines for maternal immunization are available, but studies should be conducted to evaluate their safety and efficacy, as well as regional priorities based on epidemiological data.